Low capacity for molecular detection of Alphaviruses other than Chikungunya virus in 23 European laboratories, March 2022 - Pezzi, Laura; Moegling, Ramona; Baronti, Cécile; Stanoeva, Kamelia R.; Presser, Lance D.; Jourdan, Pauline; Ayhan, Nazli; van den Akker, Willem M.R.; Zientara, Stephan; Gossner, Céline M.; Charrel, Rémi N.; Reusken, Chantal B.E.M. (PloS one, 2025)
Alphaviruses comprise over 30 identified species spread worldwide and carry a large global health burden. With vector expansion occurring in and around Europe, it is anticipated this burden will increase. Therefore, regular assessment of the diagnostic capabilities in Europe is important, e.g., by conducting external quality assessments (EQAs). Here we evaluated molecular detection of alphaviruses in expert European laboratories by conducting an EQA in March 2022. Molecular panels included 15 samples: nine alphaviruses, Barmah Forest virus (BFV), chikungunya virus (CHIKV), Eastern equine encephalitis virus (EEEV), Mayaro virus (MAYV), o’nyong-nyong virus (ONNV), Ross River virus (RRV), Sindbis virus (SINV), Venezuelan equine encephalitis virus (VEEV), and Western equine encephalitis virus (WEEV) and four negative control samples. Alphavirus detection was assessed among 23 laboratories in 16 European countries. Adequate capabilities were lacking for several viruses, and approximately half of the laboratories (11/23) relied on pan-alphavirus assays with varying sensitivity and specificity. Only 46% of laboratories characterized all EQA samples correctly. Correct result rates were > 90% for CHIKV, RRV and SINV, but laboratories lacked specificity for ONNV and MAYV and sensitivity for VEEV, BFV, and EEEV. Only two alphaviruses causing human disease circulate or have circulated in Europe, CHIKV and SINV. Molecular detection was satisfactory with both CHIKV and SINV, but < 50% correct for the entire alphaviruses panel. With continued imported cases, and a growing global concern about climate change and vector expansion, focus on progress toward rapid, accurate alphavirus diagnostics in Europe is recommended, as well as regular EQAs to monitor quality.